Peptidases released by necrotic cells control CD8+ T cell cross-priming - Jaba Gamrekelashvili; Tamar Kapanadze; Miaojun Han; Josef Wissing; Chi Ma; Lothar Jaensch; Michael P. Manns; Todd Armstrong; Elizabeth Jaffee; Ayla O. White; Deborah E. Citrin; Firouzeh Korangy; et al. (The Journal of Clinical Investigation, 2013)
Cross-priming of CD8+ T cells and generation of effector immune responses is pivotal for tumor immunity as well as for successful anticancer vaccination and therapy. Dead and dying cells produce signals that can influence Ag processing and presentation; however, there is conflicting evidence regarding the immunogenicity of necrotic cell death. We used a mouse model of sterile necrosis, in which mice were injected with sterile primary necrotic cells, to investigate a role of these cells in priming of CD8+ T cells. We discovered a molecular mechanism operating in Ag donor cells that regulates cross-priming of CD8+ T cells during primary sterile necrosis and thereby controls adaptive immune responses. We found that the cellular peptidases dipeptidyl peptidase 3 (DPP-3) and thimet oligopeptidase 1 (TOP-1), both of which are present in nonimmunogenic necrotic cells, eliminated proteasomal degradation products and blocked Ag cross-presentation. While sterile necrotic tumor cells failed to induce CD8+ T cell responses, their nonimmunogenicity could be reversed in vitro and in vivo by inactivation of DPP-3 and TOP-1. These results indicate that control of cross-priming and thereby immunogenicity of primary sterile necrosis relies on proteasome-dependent oligopeptide generation and functional status of peptidases in Ag donor cells.